2022
DOI: 10.3389/fimmu.2022.1002375
|View full text |Cite
|
Sign up to set email alerts
|

The emerging multifunctional roles of ERAP1, ERAP2 and IRAP between antigen processing and renin-angiotensin system modulation

Abstract: The Endoplasmic Reticulum Aminopeptidase 1 and 2 (ERAP1 and ERAP2) and Insulin Regulated Aminopeptidase (IRAP) are three M1 zinc metalloproteases whose role in antigen processing is the refining of peptidome either in the Endoplasmic reticulum (ERAP1 and ERAP2), or in the endosomes (IRAP). However, other novel and distinct functions are emerging. Here, we focus specifically on ERAP2. This gene has a peculiar evolutionary history, being absent in rodents and undergoing in humans to a balanced selection of two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…This hypothesis was validated in vitro a few months later [ 132 ] and, at present, we hypothesize further that ANG II upregulation is also caused by deficient endoplasmic reticulum aminopeptidase 1 and 2 (ERAP1 and ERAP2), which break down ANG II into ANG III and ANG IV ( Figure 3 ). In addition, others have shown that ANG II disrupts IL-7Rs, enabling viral thriving by inducing immune senescence [ 133 ].…”
Section: Protein Lactylation the Warburg Effect 20mentioning
confidence: 99%
See 4 more Smart Citations
“…This hypothesis was validated in vitro a few months later [ 132 ] and, at present, we hypothesize further that ANG II upregulation is also caused by deficient endoplasmic reticulum aminopeptidase 1 and 2 (ERAP1 and ERAP2), which break down ANG II into ANG III and ANG IV ( Figure 3 ). In addition, others have shown that ANG II disrupts IL-7Rs, enabling viral thriving by inducing immune senescence [ 133 ].…”
Section: Protein Lactylation the Warburg Effect 20mentioning
confidence: 99%
“…The ER harbors ERAP1 and ERAP2, zinc-metalloproteases, which have been implicated in CVD and PTSD (via OXT depletion) [ 133 , 163 , 164 ]. Indeed, ERAP2 functions as an oxytocinase, breaking down OXN and terminating its action, suggesting that a dysfunction of this enzyme may predispose it to PTSD [ 133 ].…”
Section: The Mystery Of Erap2mentioning
confidence: 99%
See 3 more Smart Citations